Obesity as a Risk Factor for Severe Covid-19 in Hospitalized Patients: Epidemiology and Potential Mechanisms - Marquez-Andrade, J (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
SARS-CoV-2 infection is a global public health problem, causing significant morbidity and mortality. Evidence shows that obesity is a recognized risk factor for hospitalization, admission to critical care units, and the development of serious complications from COVID-19. This review analyzes the available epidemiological evidence that relates obesity to a higher risk of severity and mortality from COVID-19, examining the possible pathophysiological mechanisms that explain this phenomenon on a cellular and molecular level. © 2022 by the authors.